PENGARUH PEMANFAATAN LIMBAH PLASTIK (LPDE) SEBAGAI BAHAN TAMBAHAN CAMPURAN ASPAL PADA PERKERASAN JALAN AC-WC TERHADAP NILAI MARSHALL - Putra Nanda; Helga Yermadona; Zulheldi Zulheldi (Progressive Journal of Advanced Engineering and Technology, 2026)
The type of LPDE Low Densty Polyethilen plastic waste can be used as a mixture for paved road construction in the field, for that it must be known in advance what percentage of use and type of LPDE plastic waste pieces against the weight of asphalt so that it can be ensured to meet Marshall's characteristics both for stability and deformation of asphalt. In this study, it aims to determine the effect of adding LPDE plastic waste to the asphalt mixture of test methods carried out in the Civil Engineering laboratory of UM West Sumatra using the type of LPDE plastic waste on the AC-WC layer of Asphalt Concrete-Wearing Course, using asphalt pen pertamina 60/70 and aggregate material from the Civil Engineering labor of UM West Sumatra on the marshall value. The test results showed that the use of 0%,3%,6% LPDE plastic content that meets the provisions of the 2018 Highways Technical Specification with increased stability value and VMA aggregate 16.11% in 6% plastic content, 3.43 mm flow melting in 3% plastic content and 460.60 kg MQ marshall in 6% plastic content. From the research, it can be concluded that the use of LPDE plastic waste can be used as an added material to the AC-WC asphalt mixture can reduce LPDE plastic waste pollution in Indonesia.Keywords : Plastic waste LPDE, AC-WC, Asphalt, Marshall Value